14 Foundation year 1 (fy1) doctors knowledge about common palliative medicine prescribing issues. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Holyhead, Kate; Bullock, Rachel; Willis, Derek
Abstract : Background: Death and the process of dying is an inevitable part of the practice of medicine. The ability to provide palliative care is a necessity for every junior doctor and currently approximately 60% of deaths occur in hospital. It has been suggested that current undergraduate medical education is failing to prepare junior doctors for their role in caring for dying patients. Dealing with death and talking to distressed relatives is also a major source of stress. This study aims to explore and describe the type and amount of undergraduate palliative medicine education received; to explore and describe the participant's level of confidence towards the management of patients with palliative care needs and to assess the level of prescribing knowledge when faced with common palliative care scenarios. Methods: Mixed methods questionnaires including case vignettes with single-best answer, multiple choice questions were completed under exam conditions by newly qualified junior doctors. Results: 37 FY1 doctors were included in the study. The mean time allocated to undergraduate teaching was 21 hours with a wide range of 2–140 hours. A palliative clinical placement was a component of teaching in 41% of participants. Participant-reported confidence levels varied among the four areas explored but the majority of participants responded negatively. The mean score of the knowledge component of the questionnaire was 45% (range 20%–80%). Level of participant-reported confidence demonstrated no correlation with knowledge as assessed. Conclusions: This study highlights the lack of exposure of undergraduates to patients with palliative care needs, a variable level of knowledge when faced with scenarios they are likely to encounter during foundation years, and a level of confidence in the subject which may not correlate with their practical abilities.